Downregulation of Methyltransferase-Like 14 Promotes Ovarian Cancer Cell Proliferation Through Stabilizing TROAP mRNA - Li, Yize; Peng, Hongyan; Jiang, Peng; Zhang, Jiarui; Zhao, Yongmei; Feng, Xuelian; Pang, Cui; Ren, Jingyi; Zhang, Hongmei; Bai, Wendong; Liu, Wenchao (Frontiers in Oncology, 2022)
Altered expression levels of the proteins that regulate N6-methyladenosine (m6A) RNA methylation, including methyltransferase-like 14 (METTL14), are associated with cancer development. Based on our analysis of 10 m6A methylation regulators using The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets, we focused on the regulatory role of METTL14 in ovarian cancer. We performed bioinformatics and survival analyses with these datasets and also used METTL14-overexpressing SKOV-3 ovarian cancer cells for in vitro studies. Trophinin associated protein (TROAP) siRNA and treatment with or without actinomycin D was used in the cells for qRT-PCR, western blot, cDNA microarray, cell viability, colony formation, luciferase gene reporter, methylated RNA immunoprecipitation (MeRIP)-qPCR, total RNA methylation, and RNA stability assays. Additionally, ovarian cancer and normal tissue samples were analyzed by immunohistochemistry, qRT-PCR, and western blot assays. The TCGA and GEO data confirmed gene mutations and copy number variations (CNVs) of these 10 m6A RNA methylation regulators in ovarian cancer tissues. Furthermore, reduced METTL14 expression was associated with alterations in CNVs as well as poor patient survival in ovarian cancer. Moreover, the METTL14 and m6A RNA methylation levels were both significantly reduced in ovarian cancer tissues than in normal tissues. Restoration of METTL14 expression suppresses ovarian cancer cell proliferation by inhibition of TROAP expression. Further in vivo and in vitro experiments confirmed that METTL14 is a negative regulator of ovarian cancer cell proliferation via TROAP expression and that m6A RNA methylation regulates TROAP mRNA stability. In conclusion, METTL14 overexpression decreased ovarian cancer proliferation by inhibition of TROAP expression via an m6A RNA methylation-dependent mechanism.